The Effect of Project Based Learning Model on Reading Comprehension Skills of Grade IV Students of SDIT Khairul Ikhwan - Juhari, Irfan; Wikanengsih (JLER (Journal of Language Education Research), 2025)
Abstract This study aims to identify significant differences in students' reading comprehension between those who use project-based learning model and those who use traditional learning model. The research design used was one group pretest posttest design. The instruments used in this study used test and non-test techniques. The data obtained were analyzed using descriptive statistics and inferential statistics. The object studied in this study was class IV students of SDIT Khairul Ikhwan totaling 19 people. The results showed that the significance value or Asymp. Sig. (2-tailed) or p-value of 0.001 which is smaller than the 5 percent significance level (p-value <0.05), then the decision taken is to reject H0. That is, there is a significant difference in students' reading comprehension between users of the Project Based Learning model and the traditional learning model. Keywords: Reading Comprehension, Project Based Learning